Gothic dreams and nightmares - Althofer, Jayson; Bowring, Nicola; Davison, Carol Margare; Davison, Carol; Giakaniki, Maria; Green, James Aaron; Hirst, Sam; Leeder, Murray; Lopes, Elisabete; Mills, Kirstin A.; Moore Jr, Richard W.; Musgrove, Brian; et al. (Manchester University Press, 2024)
Gothic dreams and nightmares is an edited collection on the compelling yet under-theorised subject of Gothic dreams and nightmares ranging across more than two centuries of literature, the visual arts, and twentieth- and twenty-first century visual media. Written by an international group of experts, including leading and lesser-known scholars, it considers its subject in various national, cultural, and socio-historical contexts, engaging with questions of philosophy, morality, rationality, consciousness, and creativity.